1961
DOI: 10.4141/cjss61-003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Soil Moisture Tensions on Grass and Legume Species

Abstract: Established stands of three grasses and legumes, grown in a greenhouse, were subjected to flooding treatments consisting of soil moisture tensions of approximately 0, 25 and 40 centimetres of water which were equivalent to field conditions where the water table is at the soil surface, 25 and 40 centimetres below the soil surface, respectively. Herbage and root yields were measured.Grasses were more tolerant to flooding than were the legumes. The order of decreasing tolerance to flooding was: reed canary grass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Other grass species have been shown to grow well under conditions of poor aeration. Finn et al ( 6) grew timothy, bromegrass, and reed canary grass in pots maintained at soil moisture tensions of 0, 25, and 40 centimeters of water for periods of 10,20, and 30 days. Check pots were watered to approximate field capacity.…”
Section: /Minmentioning
confidence: 99%
“…Other grass species have been shown to grow well under conditions of poor aeration. Finn et al ( 6) grew timothy, bromegrass, and reed canary grass in pots maintained at soil moisture tensions of 0, 25, and 40 centimeters of water for periods of 10,20, and 30 days. Check pots were watered to approximate field capacity.…”
Section: /Minmentioning
confidence: 99%
“…Soil moisture data collected at both sites further indicated rapid drainage of the soil profile following the end of the recharge events. Since lack of oxygen caused by prolonged flooding is directly related to development of root or plant diseases (Barta and Schmitthenner 1986;Cameron 1973;Heinrichs 1972), free drainage of the applied winter water through the root zone is important and presents one of the main risk factors when applying large amounts of water for winter recharge (Finn et al 1961).…”
Section: Application Timing Soil Oxygen Statusmentioning
confidence: 99%
“…Alfalfa can be damaged by lack of oxygen in the root zone from prolonged saturation; however, the extent of crop damage is temperature dependent (Barta 1988; Barta and Sulc 2002;Drew and Lynch 1980). Alfalfa is less susceptible to injury when temperatures are cooler, even after prolonged saturation (Barta and Schmitthenner 1986;Cameron 1973;Finn et al 1961;Heinrichs 1972).…”
mentioning
confidence: 99%
“…In greenhouse studies, Bendixen and Peterson ( 1) obtained more than a 50% reduction in dry matter production of the shoots of 1adino clover by a 9-day flooding followed by a 1-day drainage sequence. Finn et al (3) reported that forage yields usually decreased as the soil temperature under flooding increased from 40° to 80° F.…”
Section: W B Gilbert and D S Chamblee2mentioning
confidence: 99%